2016
DOI: 10.1016/j.janxdis.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive-behavioral therapy for youth anxiety on sleep problems

Abstract: The present study examined (a) whether sleep related problems (SRPs) improved following cognitive-behavioral therapy (CBT) for youth with anxiety disorders, (b) whether variables that may link anxiety and SRPs (e.g., pre-sleep arousal, family accommodation, sleep hygiene) changed during treatment, and (c) whether such changes predicted SRPs at posttreatment. Youth were diagnosed with anxiety at pretreatment and received weekly CBT that targeted their principal anxiety diagnosis at one of two specialty clinics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 156 publications
(274 reference statements)
5
46
1
Order By: Relevance
“…Such approaches should consider the likely distress arising from disconnecting, with an associated increase in pre-sleep cognitive arousal, which could be tackled with cognitive behavioral-or mindfulness-based techniques. 53,54 These novel insights can help reconcile existing evidence of both positive and negative health and wellbeing outcomes associated with social media use, as research has demonstrated that heavier users tend to report poorer sleep patterns, 3,5,18,20 but also benefits such as increased social connectedness and sense of belonging. 36,37 The current findings suggest that adolescents face a trade-off between these benefits and costs of using social media at night, and must balance the desire for inclusion and belonging in offline peer settings the following day with the need for sufficient sleep, avoiding delayed bedtimes and daytime tiredness.…”
Section: Discussionmentioning
confidence: 92%
“…Such approaches should consider the likely distress arising from disconnecting, with an associated increase in pre-sleep cognitive arousal, which could be tackled with cognitive behavioral-or mindfulness-based techniques. 53,54 These novel insights can help reconcile existing evidence of both positive and negative health and wellbeing outcomes associated with social media use, as research has demonstrated that heavier users tend to report poorer sleep patterns, 3,5,18,20 but also benefits such as increased social connectedness and sense of belonging. 36,37 The current findings suggest that adolescents face a trade-off between these benefits and costs of using social media at night, and must balance the desire for inclusion and belonging in offline peer settings the following day with the need for sufficient sleep, avoiding delayed bedtimes and daytime tiredness.…”
Section: Discussionmentioning
confidence: 92%
“…Structured CBT provides youth with specific cognitive restructuring strategies that may apply not only to daytime worries and ruminations, but also to worries and ruminations at bedtime, which are very common in anxious youth and are associated with problems with sleep (Caporino et al, 2015; Hiller, Lovato, Gradisar, Oliver, & Slater, 2014; Peterman et al, 2016; Peterman, Carper, & Kendall, 2015). However, CBT does require advanced cognitive and verbal skills on behalf of the youth, and asks parents to help youth practice the use of coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al (2015) also recommend acceptance and commitment therapy (ACT), which guides patients to increase their mindfulness, acceptance, and ability to “live in the moment” (51). A recent study examining the ability of CBT for anxiety to improve sleep related problems in an adolescent sample found parent-reported improvements in “bedtime resistance” and “sleep anxiety,” but adolescents did not report significant changes (52). For participants in our study—younger low income women, maybe the best approach is to try to address both the causes of distress in these women’s lives (improve clarity about the emotions being experienced), come to an acceptance of the emotions being experienced, and control impulsive behavior.…”
Section: Discussionmentioning
confidence: 99%